Calibration of Raman bandwidth in large Raman images using a mercury–argon lamp. (2nd December 2020) - Jakubek, Ryan S.; Fries, Marc D.
Abstract: Raman imaging has proven to be an important tool in the analysis of astromaterials. Raman imaging can describe the composition and mineralogy of astromaterials in a nondestructive manner preserving precious samples for additional study. Raman bandwidth is a common spectroscopic marker used to elucidate information such as composition, latent strain, and thermal processing history. The observed Raman bandwidth of a sample is a result of a convolution of the true Raman lineshape and the spectrometer's slit function. Thus, to compare Raman bandwidths across spectra and instruments, one needs to calibrate the Raman spectrum to account for effects of the slit function. Astromaterials are heterogeneous requiring the collection of large Raman images for adequate sampling. It is well known that the wavenumber calibration of an instrument drifts with time throughout Raman image collection. Here, we find that the spectrometer slit function also varies with time and laboratory temperature throughout Raman image collection. We utilize a mercury–argon (Hg–Ar) lamp integrated into our Raman microscope in a novel manner to calibrate the bandwidth in each Raman spectrum within our Raman image. We can do this because the narrow Hg–Ar lamp emission lines approximate the spectrometer slit function for each Raman spectrum allowing for the calculation of the true Raman bandwidth from each Raman spectrum within the Raman image. Our technique allows for the comparison of Raman bandwidth throughout a Raman image and between Raman images/spectra collected using different instruments, facilitating scientific analyses that are reproducible across multiple laboratories. Abstract : We found that the observed Raman bandwidth drifts over time and laboratory temperature. Using a mercury–argon lamp, we developed a method for calibrating Raman bandwidth across Raman images collected over long timescales. Using our calibration method, we are able to reduce the drift in observed bandwidth over long timescales and determine the true full‐width‐half‐maximum (FWHM) of the Raman bands allowing comparison of FWHM across Raman images collected using different instruments.